Acceptor-mediated regioselective enzyme catalyzed sialylation: chemoenzymatic synthesis of GAA-7 ganglioside glycan. Issue 28 (10th March 2021) - Tseng, Hsin-Kai; Su, Yung-Yu; Chang, Ting-Wei; Liu, Hsin-Chien; Li, Pei-Jhen; Chiang, Pei-Yun; Lin, Chun-Cheng
Abstract : The glycan of GAA-7 was facilely synthesized by enzymatic glycosylation through changing the nonreducing acceptor into GalNH2 or GalAz to successfully switch the regioselectivity of PmST1. Abstract : Herein, we applied PmST1 (a sialyltransferase) to achieve acceptor-mediated regioselective sialylation (AMRS) on the nonreducing end GalNH2 or GalAz (2-azido-2-deoxy galactose). Thus, C5 and C8-modified sialic acid was efficiently assembled on GalNH2 (or GalAz) to achieve the synthesis of the GAA-7 (one of the echinodermatous gangliosides with higher neuritogenic activity) glycan moiety.